1997
DOI: 10.1143/jjap.36.l1637
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Reaction of Ni with Amorphous SiGe Thin Film on SiO2

Abstract: An accelerated random sequential adsorption process is studied as a model of chemisorption on a line with precursor layer diffusion. In this process if the position first selected for deposition is occupied then the particle diffuses and is absorbed on the first vacant position it visits. For k-mer deposition exact results are obtained for the gap distribution function. Physically measurable quantities such as the average island size and the probabilities of island nucleation, growth and coagulation are calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Jin et al [13] reported the peak intensity of Si-Si bond in Raman spectra falls between 499-520 cm . Fig.8 shows the Raman spectra variations of 5 different annealing temperatures under the annealing temperature of 450°C and 500 'C.…”
Section: Resultsmentioning
confidence: 99%
“…Jin et al [13] reported the peak intensity of Si-Si bond in Raman spectra falls between 499-520 cm . Fig.8 shows the Raman spectra variations of 5 different annealing temperatures under the annealing temperature of 450°C and 500 'C.…”
Section: Resultsmentioning
confidence: 99%
“…Scientific reports on the MIC of a-Si, amorphous Ge (a-Ge), or amorphous SiGe (a-SiGe) when coming in contact with certain metals appeared in the early 1970s 14 15 or was studied with double layers of amorphous semiconductors [16][17][18][19][20] and metals/implanted metal. [21][22][23] There are two kinds of mechanisms explaining the metal-induced-crystallized a-Si: one dependent on the silicide formation metal (e.g., Pd and Ni) 24 and the other with no need for silicide formation (e.g., Al, 25 Ag, and Au).…”
Section: Introductionmentioning
confidence: 99%
“…Metal dot-arrays have been widely used in areas such as optical devices [1,2], DNA or protein electrophoresis [3], metal induced low-temperature growth of poly-silicon substrate of TFT-LCD [4,5], and catalysts for CNT growth [6][7][8]. The need to develop nano-sized dot arrays has increased tremendously during the last decade due to their excellent quantum effect, physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%